Water requirements in growth stages and effects of deficit irrigation on fruit productivity of drip irrigated Nagpur mandarin (Citrus reticulata) - SHIRGURE, P S; SRIVASTAVA, A K; HUCHCHE, A D (The Indian Journal of Agricultural Sciences, 2014)
The field experiment on irrigation scheduling based on pan evaporation replenishment through drip irrigation system was conducted to find out the water requirements in critical growth stages of 8-10 years old bearing Nagpur mandarin (Citrus reticulata Blanco) during 2009-2012 at NRC for Citrus, Nagpur. In this trial five levels of pan evaporation based irrigation schedules with respect to critical water requirement, plant growth, soil and leaf nutrient status, yield and fruit quality was investigated. The irrigations were scheduled on percent of pan evaporation replenishment (ER) in various stages of growth and fruit development. The different stages considered in this study are: Stage-I (Jan-Feb), Stage-II (Mar-Apr), Stage-III (May-Jun), Stage-IV (Jul-Aug), Stage-V (Sep-Oct) and StageIV (Nov-Dec).The treatments were irrigation schedule with 30% ER in stage-I, III, V and 40% ER in stages II, IV and VI (T1), irrigation schedule with 40% ER in stage-I, III, V and 60% ER in stages II, IV and VI (T2), irrigation schedule with 60% ER in stage-I, III, V and 80% ER in stages II, IV and VI (T3), irrigation schedule with 80% ER in stage-I to VI (T4) and irrigation schedule with 30% ER in stage-I to VI (T5) with three replications in Randomized Block Design. The study indicated that the irrigation water requirement of drip irrigated Nagpur mandarin scheduled at 80% ER in stages I to VI ranged from 35.3 to 188.1 litres during 2009-2012. The growth of plant height (4.73 m) and stock girth (66.37 cm) was more in irrigation scheduled at 80% ER in stages I to VI. There is a significant in increase in canopy volume (68.97 m3) in irrigation scheduled at 80% ER in stages I to VI. The average fruit yield recorded was 16.09 tonnes per ha. in irrigation scheduled 80% ER in stages I to VI. The average fruit weight, Total Soluble Solids, juice percentage was high in irrigation at 80% ER in stages I to VI in comparison with other irrigation schedules. The study revealed that the irrigation scheduling at critical water need affect the plant growth, yield and fruit quality of Nagpur mandarin with drip irrigation scheduling less than 80% ER in all stage.